THE USE OF INTERACTIVE WHITE BOARD IN EYL MOTIVATION - . Munjiana (Bandar Lampung University (UBL), 2016)
Young learners are usually described as learners aged between 6 to 10 or 11 years old. To teach this age group means to understand them, know what their attitudes, opinions and interests are. There are some characteristics which teachers should bear in mind when preparing activities and teaching young learners. This is a heterogeneous group with different kind of motivation for learning. It mostly depends on teachers how they introduce the subject they teach and how they attract their attention. This paper will discuss one of the newest technical equipment, the Interactive White Board (IWB), which is quickly entering schools and helping teachers with their work. The aim of this paper is to inform interactive whiteboard materials for educators teaching English as a foreign language at Primary schools. It will also look at some possible advantages and disadvantages of using IWB, how easy or difficult it is to use, what effect it has on their motivation, and what actually is so fascinating about it.